2020
DOI: 10.3390/cosmetics7010016
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Study to Determine the Sun Protection Factor of Natural Pterostilbene from Pterocarpus Marsupium

Abstract: Ultraviolet (UV) rays and its harmful effects have always been a concern to skin health. Sunscreen and sunblock prevent the harmful effects of UV radiation on the skin. Sun Protection Factor (SPF) is an indication of the sun-protective capacity of an ingredient. There is an ever increasing interest in the cosmetic industry for developing novel functional ingredients from natural sources. The purpose of this study was to determine in-vitro and in vivo SPF of natural 90% pterostilbene extracted from the dried he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…However, in the DPPH assay, the antioxidant capacity of PTS was higher than RSV; that is, the potential antioxidant activity of PTS was nine times greater than RSV. 22,16 ABTS assay was showed that the antioxidant capacity of oxy-RSV compounds was higher than PTS, RSV and pynosilvyn compounds. 6…”
Section: Duca Et Al (mentioning
confidence: 96%
See 1 more Smart Citation
“…However, in the DPPH assay, the antioxidant capacity of PTS was higher than RSV; that is, the potential antioxidant activity of PTS was nine times greater than RSV. 22,16 ABTS assay was showed that the antioxidant capacity of oxy-RSV compounds was higher than PTS, RSV and pynosilvyn compounds. 6…”
Section: Duca Et Al (mentioning
confidence: 96%
“…PTS, one of the stilbene derivatives, exists plentifully in bark fruit skin and blueberries [18][19][20][21] as well as Indian kino plants. 7,22 Meanwhile, 3-hydroxy PTS, which is one of the PTS metabolites, can be isolated from all parts of the Sphaerophysa salsula, a type of shrub widespread in Central Asia and the Western China Sea. 13 These data in aggregate provide a clear and wide variety of stilbene sources.…”
Section: Stilbene Derivatives and Their Sourcesmentioning
confidence: 99%
“…Values are reported as means ± SD of four independent determinations. The inhibition percentage was calculated by the following equation: The sun protection factor (SPF) was calculated according to the method described by Mansur et al [50] and used by other authors [51][52][53]. Briefly, the method consists of measuring the absorbance of the sample between 290 and 320 nm, every 5 nm, and using the following equation: where CF is a correction factor (10), EE (λ) is the erythemal effect spectrum, and I (λ) is the solar intensity spectrum.…”
Section: Tyrosinase Inhibitory Activitymentioning
confidence: 99%
“…Briefly, the method consists of measuring the absorbance of the sample between 290 and 320 nm, every 5 nm, and using the following equation: where CF is a correction factor (10), EE (λ) is the erythemal effect spectrum, and I (λ) is the solar intensity spectrum. The EE (λ) × I (λ) values are constant for each wavelength of the interval and they are reported in the literature (Table 4) [51][52][53]. All…”
Section: Tyrosinase Inhibitory Activitymentioning
confidence: 99%
See 1 more Smart Citation